Motivation, Persuasion and Healthy Eating: a Case Study on a Socially-Aware Persuasive System Design - Espinoza, Geovanna Evelyn Taype; Baranauskas, Maria Cecilia Calani (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Countries are confronting a variety of problems, among them those related to obesity and other illness due to uncontrolled consume of highly processed and inorganic food. Our question is: how the information systems and the human-computer interaction fields can help to improve the human behavior towards the consumption of healthy food for wellbeing? This paper searches for answers to this question with a case study in which we attempt to motivate and persuade people to eat healthy food by using an information system and, on the other hand, influence owners of restaurants to offer more healthy food. In this work we present a persuasive information system, designed using the Persuasive OpenDesign framework (a socially aware platform for open design) and discuss preliminary results of using it. We conclude this paper with future lines of work on this subject.